Optimization of surfactant concentration in carbon nanotube solutions for dielectrophoretic ceiling assembly and alignment: implications for transparent electronics - Abdulhameed, Abdullah; Halin, Izhal Abdul; Mohtar, Mohd Nazim; Hamidon, Mohd Nizar (American Chemical Society, 2022)
Surfactants such as sodium dodecyl sulfate (SDS) are used to improve the dispersity of carbon nanotubes (CNTs) in aqueous solutions. The surfactant concentration in CNT solutions is a critical factor in the dielectrophoretic (DEP) manipulation of CNTs. A high surfactant concentration causes a rapid increase in the solution conductivity, while a low concentration results in undesirably large CNT bundles within the solution. The increase in the solution conductivity causes drag velocity that obstructs the CNT manipulation process due to the electrothermal forces induced by the electric field. The presence of large CNT bundles is undesirable since they degrade the device performance. In this work, mathematical modeling and experimental work were used to optimize the concentration of the SDS surfactant in multiwalled carbon nanotube (MWCNT) solutions. The solutions were characterized using dynamic light scattering (DLS) and ultraviolet–visible spectroscopy (UV–Vis) analysis. We found that the optimum SDS concentration in MWCNT solutions for the successful DEP manipulation of MWCNTs was between 0.1 and 0.01 wt %. A novel DEP configuration was then used to assemble MWCNTs across transparent electrodes. The configuration was based on ceiling deposition, where the electrodes were on top of a droplet. The newly proposed configuration reduced the drag velocity and prevented the assembly of large MWCNT bundles. MWCNTs were successfully assembled and aligned across interdigitated electrodes (IDEs). The assembly of MWCNTs from aqueous solutions across transparent electrodes has potential use in future transparent electronics and sensor devices.